Lucjusz Anneusz Seneka – niewdzięczny syn ziemi hiszpańskiej - Danek, Zbigniew (Collectanea Philologica, 2022)
The author of this article discusses the question to what extent Lucius Annaeus Seneca – born in Hispania, and today exceptionally venerated in this country as a precursor of the “Spanish” mentality – felt he belonged to this land, and to what extent his feelings towards it were expressed in his writings. An analysis of his creative output leads to the conclusion that he felt little affection for the land of Hispania, since in his writings there are almost no references to it, and perhaps the only trace of his connection with his native country is his youthful epigram Ad Cordubam, in which, however, he shows more warmth towards himself than towards the city. The perceived lack of any more significant declarations of “Spanish” nationality, however, does not so much testify to his pettiness as to his stoic distance from the ethnic and political barriers that divide the community of mankind that constitutes a whole for him.